Fluidized bed reactor for preparing carbon nanotubes by industrial mixed hydrocarbon section temperature control coupling partition catalysis and preparation method
Patent Information
- Application Number
- CN202611229124.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-27
AI Technical Summary
[0002]碳纳米管凭借优异的导电、导热与力学性能,在电化学储能、电催化、复合增强材料等领域具备极高应用价值;石化炼制、煤化工及高分子热解过程副产大量包含气态低碳轻烃、混合苯系芳烃、重质柴油油品的工业混合烃废料,是低成本碳源的优质资源化原料,当前行业主流采用流化床催化裂解工艺以混合烃制备碳纳米管;但现有成套制备技术仍存在诸多难以克服的工业化瓶颈;其一,液态重质烃原料直接通入反应器易出现气化不均、液滴直触催化剂现象,行业普遍采用气液两路独立进料方式,反应器内部原料组分分布不均,局部反应剧烈生成大量无定形碳杂质;其二,工业混杂混合烃原料组分复杂、批次波动大,现有工艺需配套精馏、分相等复杂预处理工序才能投入反应,工艺流程冗长、生产综合成本偏高;其三,单一温场、单一催化体系制备所得碳纳米管产物管径分布杂乱、团聚缠绕严重,产物纯度偏低,原料组分小幅波动即会造成产品形貌、热稳定性大幅劣化,难以满足连续化稳定工业化生产的需求
本发明提供的分段温控分区催化流化床反应器,通过沿气流方向分区设置独立温控的预裂解区与成型反应区、分层装填参数限定且功能差异化、装填顺序不可调换的多级孔镁铝复合氧化物负载Fe-Ni双金属催化剂与γ-氧化铝负载Co-Mo-Ni三元金属催化剂,打破行业内两类催化剂活性温度区间冲突无法联用的固有偏见,依靠两级催化剂协同作用,下层多级孔镁铝复合氧化物负载Fe-Ni双金属催化剂利用多级孔道缓冲裂解速率、低温抑制轻质烃瞬时爆碳,并完成重质长链烃初步断链活化,上层γ-氧化铝负载Co-Mo-Ni三元金属催化剂在专属高温区间驱动烃中间体深度裂解、引导碳原子有序规整沉积,显著降低无定形碳杂质生成量,即便原料组分大幅波动,产物碳纳米管纯度仍稳定维持在45 %以上,最优工况下纯度可达62.30 %,所得碳纳米管管径分布窄、团聚缠绕少、晶格缺陷少、高温热稳定性能优异。由此实现工业废弃烃料资源化循环利用、降低碳纳米管量产成本的同时,产出高品质规整碳纳米管,能够稳定适配电化学储能、电催化、复合材料增强等多领域工业化应用需求,兼具突出的经济效益与环保价值。
Smart Images

Figure CN122974221A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of industrial mixed hydrocarbon synthesis of high-value carbon materials, and in particular to a fluidized bed reactor and preparation method for the staged temperature-controlled coupled zoned catalytic preparation of carbon nanotubes from industrial mixed hydrocarbons. Background Technology
[0002] Carbon nanotubes, with their excellent electrical, thermal, and mechanical properties, possess immense application value in fields such as electrochemical energy storage, electrocatalysis, and composite reinforcement materials. Petrochemical refining, coal chemical processes, and polymer pyrolysis produce large quantities of industrial mixed hydrocarbon waste containing gaseous low-carbon light hydrocarbons, mixed benzene aromatics, and heavy diesel oil. This waste is a high-quality, low-cost carbon source. Currently, the mainstream industry method is fluidized bed catalytic cracking to prepare carbon nanotubes from mixed hydrocarbons. However, existing complete preparation technologies still face several insurmountable industrialization bottlenecks. Firstly, directly introducing liquid heavy hydrocarbon feedstock into the reactor easily leads to uneven gasification and direct contact between droplets and the catalyst. The industry generally adopts a gas-liquid dual-feed method, resulting in uneven distribution of raw material components inside the reactor and violent local reactions that generate a large amount of amorphous carbon impurities. Secondly, the industrial mixed hydrocarbon raw materials have complex components and large batch fluctuations. Existing processes require complex pretreatment processes such as distillation and phase separation before they can be put into the reaction, resulting in a lengthy process flow and high overall production costs. Thirdly, carbon nanotube products prepared by a single temperature field and a single catalytic system have disordered tube diameter distribution, severe agglomeration and entanglement, and low product purity. Even small fluctuations in raw material components can cause significant deterioration in product morphology and thermal stability, making it difficult to meet the requirements of continuous and stable industrial production.
[0003] Therefore, there is an urgent need to develop a new type of preparation equipment and supporting process that can be adapted to industrial mixed hydrocarbon feedstocks and simultaneously solve multiple problems such as uneven feeding, mismatch between light and heavy hydrocarbon cracking, high impurity content, and high raw material pretreatment costs. Summary of the Invention
[0004] To address the problems existing in the background art, the present invention provides a fluidized bed reactor and preparation method for the segmented temperature-controlled coupled zoned catalytic preparation of carbon nanotubes from industrial mixed hydrocarbons, thereby solving at least one of the aforementioned technical problems.
[0005] The specific details of the invention are as follows: In a first aspect, the present invention provides a fluidized bed reactor for the segmented temperature-controlled coupled zoned catalytic preparation of carbon nanotubes from industrial mixed hydrocarbons. The reactor is provided with a pre-pyrolysis zone and a forming reaction zone. The pre-pyrolysis zone is close to the reaction gas inlet, and the forming reaction zone is adjacent to the pre-pyrolysis zone. The pre-pyrolysis zone is equipped with a first catalyst, and the forming reaction zone is equipped with a second catalyst; The pre-pyrolysis zone and the molding reaction zone are equipped with independent temperature control components; The first catalyst is selected from a hierarchical porous magnesium-aluminum composite oxide supported Fe-Ni bimetallic catalyst; The second catalyst is selected from γ-alumina supported Co-Mo-Ni ternary metal catalysts.
[0006] Optionally, in the first catalyst, the specific surface area of the hierarchical porous magnesium-aluminum composite oxide is 180 m². 2 / g~320m 2 / g, total pore volume 0.35 cm³ 3 / g~0.65 cm 3 The molar ratio of Fe to Ni is 1:3 to 3:1; the total loading of Fe-Ni bimetallic compounds is 6 wt% to 18 wt%, and the mass ratio of Fe to Ni is 2:1 to 1:2.
[0007] Optionally, in the second catalyst, the specific surface area of the γ-alumina support is 260 m². 2 / g~400 m 2 / g, total pore volume is 0.4 cm³ 3 / g~0.7 cm 3 / g; the total loading of Co, Mo and Ni metals is 4 wt% to 15 wt%, and the mass ratio of Co, Mo and Ni is 3:1:2 to 5:2:1.
[0008] Optionally, in the first catalyst, the molar ratio of Mg to Al in the hierarchical porous magnesium-aluminum composite oxide is 1:2, the total loading of Fe-Ni bimetal is 12 wt%, and the mass ratio of Fe to Ni is 1:1; In the second catalyst, the total loading of Co, Mo, and Ni metals is 9 wt%, and the mass ratio of Co, Mo, and Ni is 4:2:1.
[0009] Optionally, the mass ratio of the first catalyst to the second catalyst is 1:2 to 2:1.
[0010] Secondly, the present invention provides a method for preparing carbon nanotubes by segmented temperature-controlled coupled partitioned catalysis of industrial mixed hydrocarbons, the method comprising: The temperature of the pre-pyrolysis zone of the reactor described in the first aspect is controlled at 650 ℃ to 700 ℃, and the temperature of the forming reaction zone is controlled at 750 ℃ to 800 ℃. Liquid hydrocarbon feedstock in industrial mixed hydrocarbon feedstock is completely vaporized into gaseous material, and then mixed with gaseous low-carbon hydrocarbon feedstock. The resulting homogeneous mixed reaction gas is fed into the reactor through the reaction gas inlet along with the carrier gas. The homogeneous mixed reaction gas is then catalyzed by the first catalyst packed in the pre-cracking zone and the second catalyst packed in the forming reaction zone to obtain carbon nanotubes.
[0011] Optionally, the carrier gas is selected from nitrogen.
[0012] Optionally, the flow rate of the carrier gas is 500 mL / min to 800 mL / min.
[0013] Optionally, the purity of carbon nanotubes in the solid product obtained by conversion is not less than 45%.
[0014] Optionally, the industrial mixed hydrocarbon feedstock is derived from the resource recovery materials of coal chemical tail gas, polymer pyrolysis waste liquid, or petrochemical waste oil.
[0015] This invention provides a fluidized bed reactor for the staged temperature-controlled coupled zoned catalytic preparation of carbon nanotubes from industrial mixed hydrocarbons. The reactor comprises a pre-pyrolysis zone and a forming reaction zone. The pre-pyrolysis zone is located near the reactant gas inlet, and the forming reaction zone is adjacent to the pre-pyrolysis zone. A first catalyst is disposed in the pre-pyrolysis zone, and a second catalyst is disposed in the forming reaction zone. Independent temperature control components are provided for the pre-pyrolysis zone and the forming reaction zone. The first catalyst is selected from a hierarchical porous magnesium-aluminum composite oxide supported Fe-Ni bimetallic catalyst; the second catalyst is selected from a γ-alumina supported Co-Mo-Ni ternary metal catalyst. Compared with the prior art, this invention has the following advantages: The segmented temperature-controlled zoned catalytic fluidized bed reactor provided by this invention, through the independent temperature-controlled pre-pyrolysis zone and forming reaction zone along the airflow direction, the layered loading parameters are limited and functionally differentiated, and the loading order is non-changeable, using a multi-level porous magnesium-aluminum composite oxide-supported Fe-Ni bimetallic catalyst and a γ-alumina-supported Co-Mo-Ni ternary metal catalyst. This breaks the industry's inherent prejudice that the two types of catalysts cannot be used together due to conflicting activity temperature ranges. Relying on the synergistic effect of the two catalysts, the lower-level multi-level porous magnesium-aluminum composite oxide-supported Fe-Ni bimetallic catalyst utilizes multi-level pores to buffer the pyrolysis rate, suppress instantaneous carbon explosion of light hydrocarbons at low temperatures, and complete the initial chain-breaking activation of heavy long-chain hydrocarbons. The upper-level γ-alumina-supported Co-Mo-Ni ternary metal catalyst drives deep pyrolysis of hydrocarbon intermediates and guides the orderly and regular deposition of carbon atoms within a dedicated high-temperature range, significantly reducing the generation of amorphous carbon impurities. Even with significant fluctuations in the raw material composition, the purity of the product carbon nanotubes remains stably maintained above 45%, and under optimal conditions, the purity can reach 62.30%. The resulting carbon nanotubes exhibit narrow diameter distribution, minimal agglomeration and entanglement, few lattice defects, and excellent high-temperature thermal stability. This enables the resource-based recycling of industrial waste hydrocarbons, reduces the cost of mass production of carbon nanotubes, and produces high-quality, well-ordered carbon nanotubes. These nanotubes are stably adapted to industrial applications in various fields such as electrochemical energy storage, electrocatalysis, and composite material reinforcement, demonstrating both significant economic benefits and environmental value. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 The image shows a scanning electron microscope (SEM) image of the carbon nanotubes obtained by the preparation method of this embodiment of the invention; Figure 2 A columnar comparison chart of the purity of carbon nanotubes obtained by the preparation method of the present invention is shown; Figure 3 Thermogravimetric curves of the carbon nanotube products obtained by the preparation method of the present invention are shown. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, any product that is the same as or similar to the present invention, derived by anyone under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention. Furthermore, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of the present invention.
[0019] Specific experimental steps or conditions are not specified in the embodiments; they can be performed according to the conventional experimental steps or conditions described in the prior art. Reagents and other instruments used, unless otherwise specified, are all commercially available conventional reagent products. Furthermore, the accompanying drawings are merely illustrative diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the drawings denote the same or similar parts, and therefore, repeated descriptions of them will be omitted. Some block diagrams shown in the drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0020] Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of this specification.
[0021] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0022] Traditional fluidized beds use a single isothermal reaction chamber with a single catalyst system, which cannot meet the differentiated cracking requirements of light and heavy hydrocarbons. Light small molecule hydrocarbons rapidly and instantaneously precipitate and deposit carbon under high temperature conditions, while long-chain heavy hydrocarbons are not fully activated by bond breaking under low temperature conditions. Moreover, the industry has long suffered from the inherent technical bias of conflicting activity temperature ranges of Fe-Ni bimetallic catalysts and Co-Mo-Ni ternary catalysts, which cannot be used in a layered series for synergistic purposes. Using Fe-Ni catalyst alone can only achieve low-temperature carbon suppression but cannot drive the orderly formation of carbon atoms into tubes. Using Co-Mo-Ni ternary catalyst alone has no cracking rate limiting buffer function, and light hydrocarbons are prone to carbon explosion and the generation of flocculent impurities. In view of this, the present invention addresses the structural defects of traditional fluidized bed reactors that are single-chamber isothermal and only filled with a single catalyst. From the equipment structure level, the reactor is designed with a pre-pyrolysis zone and a shaping reaction zone sequentially arranged along the gas flow direction. Each zone is equipped with an independent temperature control component and is filled with a functionally differentiated catalyst: the pre-pyrolysis zone at the reaction gas inlet is loaded with a multi-level porous magnesium-aluminum composite oxide-supported Fe-Ni bimetallic catalyst, while the downstream shaping reaction zone is loaded with a γ-alumina-supported Co-Mo-Ni ternary metal catalyst. This solves the core technical problem that a single reaction space cannot simultaneously achieve low-temperature pre-activation of heavy hydrocarbons, suppression of carbon explosion in light hydrocarbons, and high-temperature ordered tube formation of carbon atoms—two differentiated catalytic reactions—and the industry's generally accepted inability to use Fe-Ni and Co-Mo-Ni catalysts due to conflicting activity temperature zones. The specific embodiments of the present invention are described in detail below: In a first aspect, the present invention provides a fluidized bed reactor for the segmented temperature-controlled coupled zoned catalytic preparation of hyperstructured carbon nanotubes from industrial mixed hydrocarbons. The reactor is provided with a pre-pyrolysis zone and a forming reaction zone. The pre-pyrolysis zone is close to the reaction gas inlet, and the forming reaction zone is adjacent to the pre-pyrolysis zone. The pre-pyrolysis zone is equipped with a first catalyst, and the forming reaction zone is equipped with a second catalyst; The pre-pyrolysis zone and the molding reaction zone are equipped with independent temperature control components; The first catalyst is selected from a hierarchical porous magnesium-aluminum composite oxide supported Fe-Ni bimetallic catalyst; The second catalyst is selected from γ-alumina supported Co-Mo-Ni ternary metal catalysts.
[0023] In practice, gaseous industrial mixed hydrocarbons enter the pre-cracking zone at the reaction gas inlet. The Fe-Ni bimetallic catalyst supported by a hierarchical porous magnesium-aluminum composite oxide buffers the cracking rate, suppressing the instantaneous large-scale precipitation of amorphous carbon from small-molecule low-carbon hydrocarbons, while simultaneously completing the initial chain-breaking activation of long-chain heavy diesel hydrocarbons. The activated hydrocarbon intermediates rise with the gas flow to the independently temperature-controlled forming zone, where highly dispersed Co-Mo-Ni ternary catalytic sites in a Co-Mo-Ni ternary metal catalyst supported by γ-alumina drive the orderly and regular deposition of carbon atoms into tubes. The independent temperature-controlled structure of the two zones can be matched with the exclusive optimal activity temperature windows of the two types of catalysts, breaking the industry's inherent prejudice that the conflicting activity ranges of the two types of catalysts cannot be used synergistically. This constructs a dedicated reactor adapted to the stepwise cracking of mixed hydrocarbons, realizing the separation of the two-step reaction space of pre-cracking rate limiting and impurity suppression and high-temperature orderly tube formation, providing an equipment foundation for the stable preparation of low-impurity, high-order carbon nanotubes.
[0024] It should be noted that, in the fluidized bed reactor of the present invention, a high-temperature resistant porous ceramic sieve plate or alloy grid is set as a partitioning component between the pre-pyrolysis zone and the forming reaction zone along the axial airflow direction. The pore size of the partition is smaller than the minimum particle size of the two layers of catalyst particles. On the one hand, it can ensure the unobstructed flow of carrier gas and homogeneous mixed hydrocarbon gaseous material from bottom to top. On the other hand, it can completely block the upward movement of the first catalyst particles in the lower layer and the downward sedimentation and mixing of the second catalyst in the upper layer. The partition is sealed and fixed to the reactor cylinder wall, physically isolating the axial space inside the reactor into two independent sealed reaction chambers. The lower chamber is the pre-pyrolysis zone and the upper chamber is the forming reaction zone. The two zones are equipped with independent heating and temperature control modules and temperature measuring elements, realizing that the two temperature fields do not interfere with each other and are independently and accurately controlled. From the hardware structure, the reaction sequence of the reactants first undergoing low-temperature pre-pyrolysis and then high-temperature forming is ensured, preventing the mixing of the two layers of catalyst and the filling The problem of catalytic synergistic failure caused by the reversal of the reaction sequence is addressed. The carbon nanotube product is collected in two separate systems: solid bed product and tail gas byproduct. The solid carbon nanotubes are attached to the catalyst surface of the two catalytic beds. A sealed solid product collection chamber is set at the bottom of the reactor. The entire reaction process is maintained with high-purity nitrogen to maintain an inert and oxygen-free atmosphere inside the reactor. After the reaction, nitrogen is continuously introduced to gradually cool the pre-cracking zone and the forming reaction zone to room temperature in stages to prevent the high-temperature carbon nanotubes from being oxidized and lost when exposed to air. After the equipment has completely cooled down, the sealed collection chamber at the bottom is opened to remove all the solid material in the bed at once. After simple separation, high-order carbon nanotube crude product can be obtained. The unreacted hydrocarbon tail gas discharged from the top of the reactor is introduced into the rear condenser to condense and recover recyclable hydrocarbon components. The remaining tail gas is discharged after meeting the standards, avoiding product dust and secondary introduction of impurities, and completely preserving the high-purity carbon nanotube product.
[0025] In some embodiments, the specific surface area of the hierarchical porous magnesium-aluminum composite oxide in the first catalyst is 180 m². 2 / g~320 m2 / g, total pore volume 0.35 cm³ 3 / g~0.65 cm 3 The molar ratio of Fe to Ni is 1:3 to 3:1; the total loading of Fe-Ni bimetallic compounds is 6 wt% to 18 wt%, and the mass ratio of Fe to Ni is 2:1 to 1:2.
[0026] In practice, the specific surface area of the multi-level porous magnesium-aluminum composite oxide carrier is controlled at 180 m². 2 / g~320 m² / g, total pore volume 0.35 cm³ 3 / g~0.65 cm 3 / g, combined with a Mg to Al molar ratio of 1:3 to 3:1, can construct a multi-level porous structure, which prolongs the residence time of gaseous materials by relying on the pores, thus slowing down the instantaneous carbon evolution rate of light hydrocarbons; at the same time, it can regulate the acid-base site balance on the support surface to meet the bond breaking and activation requirements of long-chain heavy hydrocarbons; the total Fe-Ni bimetallic loading of 6 wt% to 18 wt% and the limited Fe to Ni mass ratio of 2:1 to 1:2 can precisely regulate the low-temperature cracking activity, avoiding insufficient catalytic activity due to too low metal loading and metal particle agglomeration and deactivation due to too high loading.
[0027] In some embodiments, the specific surface area of the γ-alumina support in the second catalyst is 260 m². 2 / g~400 m 2 / g, total pore volume is 0.4 cm³ 3 / g~0.7 cm 3 / g; the total loading of Co, Mo and Ni metals is 4 wt% to 15 wt%, and the mass ratio of Co, Mo and Ni is 3:1:2 to 5:2:1.
[0028] In specific implementation, this invention uses a high specific surface area / total pore volume γ-alumina carrier, which can provide sufficient dispersion sites for the Co, Mo, and Ni ternary metal active components, avoiding metal agglomeration and the formation of carbon sphere impurities. Among the Co, Mo, and Ni ternary metal active components, the Mo component enhances the deep bond-breaking and cleavage ability of hydrocarbon macromolecules, while the Co and Ni components synergistically guide the orderly and directional deposition of carbon atoms generated by cleavage, avoiding the formation of disordered amorphous flocculent carbon. The total loading of Co, Mo, and Ni metals directly affects the purity and microstructure regularity of the product. After extensive experimental research, this invention has confirmed that the total loading of Co, Mo, and Ni metals is 4 wt% to 15 wt%, which avoids metal agglomeration while ensuring that the carbon nanotubes in the product are orderly and regularized, reducing the impurity content, and significantly improving the purity and microstructure regularity of the product.
[0029] In some embodiments, in the first catalyst, the Mg to Al molar ratio of the hierarchical porous magnesium-aluminum composite oxide is preferably 1:2, the total Fe-Ni bimetallic loading is preferably 12 wt%, and the mass ratio of Fe to Ni is preferably 1:1; In the second catalyst, the total loading of Co, Mo, and Ni metals is preferably 9 wt%, and the mass ratio of Co, Mo, and Ni is preferably 4:2:1.
[0030] In some embodiments, the mass ratio of the first catalyst to the second catalyst is 1:2 to 2:1. This ratio range balances the buffer capacity of the low-temperature pre-cracking bed material with the total number of active sites in the high-temperature forming bed. When the proportion of the Fe-Ni bimetallic catalyst in the lower layer is too low, heavy hydrocarbons cannot be fully pre-activated and are prone to violent cracking and generating a large number of impurities when directly entering the high-temperature zone. When the proportion of the Co-Mo-Ni ternary metal catalyst in the upper layer is too low, hydrocarbon intermediates cannot be completely and orderly deposited, resulting in a significant decrease in tube forming efficiency. This ratio range can stabilize the balance of the two-stage catalytic material ratio in the reactor. Regardless of the fluctuations in the light hydrocarbon and heavy diesel hydrocarbon components in the feedstock, the matching degree of the pre-cracking and high-temperature forming reactions can be maintained, avoiding a significant decline in product purity due to an imbalance in the loading ratio.
[0031] Secondly, the present invention provides a method for preparing hyperregular carbon nanotubes by segmented temperature-controlled coupled partitioned catalysis of mixed hydrocarbons, the method comprising: The temperature of the pre-pyrolysis zone of the reactor described in the first aspect is controlled at 650 ℃ to 700 ℃, and the temperature of the forming reaction zone is controlled at 750 ℃ to 800 ℃. Liquid hydrocarbon feedstock in industrial mixed hydrocarbon feedstock is completely vaporized into gaseous material, and then mixed with gaseous low-carbon hydrocarbon feedstock. The resulting homogeneous mixed reaction gas is fed into the reactor through the reaction gas inlet along with the carrier gas. The homogeneous mixed reaction gas is then catalyzed by the first catalyst packed in the pre-cracking zone and the second catalyst packed in the forming reaction zone to obtain carbon nanotubes.
[0032] In practice, all liquid mixed hydrocarbons are completely vaporized and then homogenized with gaseous low-carbon hydrocarbons to eliminate local concentration differences in the raw materials from the source. The gradient temperature fields of 650℃~700℃ in the pre-cracking zone and 750℃~800℃ in the forming reaction zone are controlled to match the optimal activity temperatures of the two catalyst layers respectively. Finally, the mixed gas is fed into the reactor from the bottom along with the carrier gas, and sequentially passes through the pre-cracking and forming catalytic beds for stepwise reactions. This first completes the chain breaking of heavy hydrocarbons and the slow carbon release of light hydrocarbons, and then achieves deep cracking of intermediates and ordered carbon atom tube formation. The preparation scheme provided by this invention couples the homogenization and blending of front-end raw materials, the gradient temperature field of the reactor, and the zoned dual-catalytic system. It eliminates the need for distillation separation and refining pretreatment of industrial mixed hydrocarbons, allowing for direct feeding. It simultaneously solves the two major problems of instantaneous carbon explosion in light hydrocarbons and incomplete cracking of heavy hydrocarbons, significantly reducing amorphous carbon impurities and adapting to the continuous production of waste hydrocarbon raw materials with fluctuating components in coal chemical and petrochemical industries.
[0033] It should be noted that this invention is equipped with a liquid feedstock gasification device and a homogenizing mixing buffer tank. The liquid feedstock complete gasification unit is used to completely gasify the liquid hydrocarbon feedstock in the industrial mixed hydrocarbon feedstock into gaseous material. The homogenizing mixing buffer tank is used to mix the completely gasified liquid hydrocarbon feedstock with the gaseous low-carbon hydrocarbon feedstock, so as to achieve a unified feeding after the gas-liquid hydrocarbon feedstock is fully premixed. This solves the problem of local reaction imbalance caused by the separate gas-liquid feeding and uneven gasification in traditional processes from the root. There is no need to carry out complex refining pretreatment such as distillation and phase separation of industrial mixed hydrocarbon feedstock. It can directly utilize industrial by-products such as coal chemical tail gas, polymer pyrolysis waste liquid, and petrochemical waste oil, which significantly reduces the feedstock pretreatment process and production costs. The carrier raw materials used for the reactor catalyst can be commercially purchased, and the raw materials are readily available and the cost is controllable. The modification can be completed by simply adding a gasification and mixing unit to the existing fluidized bed production line. The equipment modification cost is low, the whole process has strong resistance to feedstock fluctuations, and can operate continuously and steadily for a long time.
[0034] In some embodiments, the carrier gas is selected from nitrogen. Nitrogen serves as an inert protective atmosphere, completely isolating oxygen within the reactor and preventing high-temperature oxidation and deactivation of active metallic components such as Fe, Ni, Co, and Mo. Nitrogen acts only as a material transport carrier, does not participate in the hydrocarbon cracking reaction, and does not additionally alter the carbon evolution rate. After the reaction, nitrogen is continuously used for purging and gradient cooling, which also prevents high-temperature carbon nanotubes from oxidizing and losing weight upon contact with air, thus improving the thermal stability of the product. This process protects the active sites of bimetallic and ternary metal catalysts throughout, ensuring stable and orderly growth of carbon nanotubes and avoiding the problems of decreased product purity and rapid catalyst failure caused by oxidizing and reducing carrier gases.
[0035] In some embodiments, the flow rate of the carrier gas is 500 mL / min to 800 mL / min. By adjusting the flow rate of the carrier gas, the residence time of the mixed gas in the two catalytic beds can be precisely controlled, ensuring that the pre-cracking zone has sufficient time to complete the activation of heavy hydrocarbons and slow down the carbon deposition rate of light hydrocarbons. At the same time, the hydrocarbon intermediates can fully contact the three-way catalytic sites in the forming zone to complete the orderly tube formation, which is suitable for long-term continuous steady-state production conditions in industry.
[0036] In some embodiments, the purity of carbon nanotubes in the solid product obtained by conversion is not less than 45%.
[0037] In some embodiments, the industrial mixed hydrocarbon feedstock is derived from resource recovery materials such as coal chemical tail gas, polymer pyrolysis waste liquid, or petrochemical waste oil.
[0038] To enable those skilled in the art to more clearly understand the present invention, the following embodiments are provided to illustrate in detail the fluidized bed reactor and preparation method for the staged temperature-controlled coupled partitioned catalytic preparation of carbon nanotubes using mixed hydrocarbons.
[0039] Example 1 The segmented temperature-controlled zoned catalytic fluidized bed reactor of this invention is equipped with a high-temperature resistant silicon carbide porous sieve plate inside the reactor to achieve physical separation between the pre-pyrolysis zone and the forming reaction zone. The sieve plate pore size is smaller than the minimum particle size of the two types of catalyst particles, which can prevent the catalyst from mixing between the upper and lower parts. The two zones are equipped with independent heating modules and temperature measuring elements to achieve independent temperature control of the two zones. The first catalyst is loaded into the lower pre-pyrolysis zone of the reactor, and the second catalyst is loaded into the upper forming reaction zone. The total catalyst loading is 10 g, with 5 g of the first catalyst and 5 g of the second catalyst. The primary catalyst is a hierarchical porous magnesium-aluminum composite oxide supported Fe-Ni bimetallic catalyst. The magnesium-aluminum hierarchical porous support is a commercially available material with a Mg:Al molar ratio of 1:2 and a specific surface area of 240 m². 2 / g, total pore volume 0.48 cm³ 3 / g, a magnesium-aluminum hierarchical porous carrier was loaded with Fe-Ni bimetallic active components by equal volume impregnation method, with a total Fe-Ni metal loading of 12 wt% and a Fe to Ni mass ratio of 1:1. After impregnation and drying, it was calcined at 500 ℃ for 3 h. The second catalyst is a γ-alumina-supported Co-Mo-Ni ternary metal catalyst, with a specific surface area of 330 m² for the commercially available γ-alumina support. 2 / g, total pore volume 0.55 cm³ 3 / g, the γ-alumina support was loaded with Co-Mo-Ni ternary metals using a stepwise impregnation process. First, the molybdenum precursor was impregnated and dried, then the co-cobalt and nickel precursors were co-impregnated, and finally calcined at 550 ℃ for 3 h. The total loading of Co, Mo and Ni metals was 9 wt%, and the mass ratio of Co:Mo:Ni was 4:2:1. Industrial mixed hydrocarbons recovered from petrochemical waste oil were selected as the reaction raw materials. The mass ratio of gaseous low-carbon hydrocarbons, mixed benzene aromatic hydrocarbons (benzene 45%, toluene 30%, xylene 15%, phenol 10%), and heavy diesel hydrocarbons in the raw materials was 3:5:2. First, all liquid hydrocarbons were passed into a gasification device to be completely converted into gaseous materials. Then, they were passed into a homogenizing mixing buffer tank and thoroughly mixed to obtain a homogeneous mixed reaction gas. High-purity nitrogen was used as the carrier gas, with a flow rate of 500 mL / min. The nitrogen was continuously introduced into the reactor to purge the internal air for 15 min. After the purge was completed, the temperature was increased, and the pre-pyrolysis zone was kept at a constant temperature of 680 ℃ and the forming reaction zone at a constant temperature of 760 ℃. After the temperatures of the two zones stabilized, a homogeneous mixed gas was continuously fed from the bottom of the reactor along with the nitrogen carrier gas. The material passed through the pre-pyrolysis zone and the forming reaction zone from bottom to top, and the reaction was carried out continuously at a constant temperature for 90 min. An inert nitrogen atmosphere was maintained throughout the reaction. After the reaction was completed, nitrogen was continuously introduced to gradually cool the reactor to room temperature. The sealed solid product collection chamber at the bottom of the reactor was opened, and the solid material in the bed was taken out. Carbon nanotube products were obtained by separation with a purity of 62.30%.
[0040] Example 2 The difference from Example 1 is that the reactants used in this example consist of gaseous low-carbon hydrocarbons, mixed benzene aromatics (45% benzene, 30% toluene, 15% xylene, and 10% phenol), and heavy diesel hydrocarbons. The total proportion of gaseous low-carbon hydrocarbons and mixed benzene aromatics is increased to 85%, and the proportion of heavy diesel hydrocarbons is 15%. The catalyst system, loading amount, preparation parameters, and other implementation processes are consistent with those in Example 1. The mixed gas reacts stably in the segmented catalytic system, effectively avoiding the problem of instantaneous carbon deposition of small molecule feedstocks.
[0041] Test results: The carbon nanotube product has a purity of 56.72%, with no large, disordered carbon impurities, and the product structure is highly uniform.
[0042] Example 3 The difference from Example 1 is that the reactants used in this example consist of gaseous low-carbon hydrocarbons, mixed benzene aromatics (45% benzene, 30% toluene, 15% xylene, and 10% phenol), and heavy diesel hydrocarbons. The total proportion of gaseous low-carbon hydrocarbons and mixed benzene aromatics is reduced to 60%, and the proportion of heavy diesel hydrocarbons is 40%. The catalyst system, loading amount, preparation parameters, and other implementation processes are consistent with Example 1. Under this feedstock system, the segmented catalyst can suppress the high-temperature cracking of heavy components to produce amorphous carbon.
[0043] Test results: The purity of the carbon nanotube product was 48.68%, the long-chain hydrocarbons were fully cracked, and the tube formation efficiency was better than that of the traditional single isothermal process.
[0044] Example 4 The difference from Example 1 is that the reactants used in this example consist of gaseous low-carbon hydrocarbons, mixed benzene aromatics (45% benzene, 30% toluene, 15% xylene, and 10% phenol), and heavy diesel hydrocarbons, with the total proportion of gaseous low-carbon hydrocarbons and mixed benzene aromatics being 75% and heavy diesel hydrocarbons being 25%. The catalyst system, loading amount, preparation parameters, and other implementation processes are consistent with those in Example 1. The mixed gas can stably and continuously synthesize carbon nanotubes in a segmented catalytic system.
[0045] Test results: The purity of the carbon nanotube product was 45.91%, the carbon nanotubes had regular morphology and excellent thermal stability.
[0046] See Figure 1 The scanning electron microscope (SEM) images shown are, in which (a), (b), (c), and (d) are SEM images of the carbon nanotube materials obtained in Examples 1-4, respectively. Figure 1 As shown, characterization results indicate that the carbon nanotubes in the product have a uniform diameter distribution, no large amount of amorphous carbon flocs or metal agglomerates, low degree of carbon nanotube entanglement and agglomeration, and excellent microstructure regularity.
[0047] See Figure 2 The bar chart showing the purity comparison of the crude carbon nanotube products is as follows: Example 1 uses a standard ratio of balanced mixed hydrocarbon feedstock, with the proportions of light, aromatic, and heavy diesel components adapted to the synergistic reaction range of the bilayer catalyst. The lower Fe-Ni hierarchical porous catalyst effectively suppresses instantaneous carbon explosion of light hydrocarbons and completes the pre-activation of heavy hydrocarbons, while the upper Co-Mo-Ni ternary catalyst efficiently drives the orderly deposition of carbon atoms, resulting in the lowest amount of amorphous impurities and a product purity reaching the peak of 62.30% under all operating conditions. Example 2 uses a mixed hydrocarbon feedstock with a higher proportion of light components, significantly increasing the proportion of small-molecule low-carbon hydrocarbons. Relying on the buffering and regulation effect of the hierarchical channels of the lower catalyst on the cracking rate, a large amount of flocculent amorphous carbon is avoided from instantaneously generating, and the product purity only slightly decreases to 56.72%, without a cliff-like decline in purity. Example 3 uses a feedstock condition with a medium proportion of heavy diesel, increasing the proportion of long-chain heavy hydrocarbons to 35%. The cracking and activation difficulty of long-chain hydrocarbons increases, and a small amount of incomplete cracking intermediates generate trace impurities, resulting in a product purity of 48.68%. %; Example 4 is an extreme feedstock condition with a high proportion of heavy diesel oil. The proportion of heavy diesel oil hydrocarbons reaches 50%. Even though the feedstock is mainly composed of long-chain hydrocarbons that are difficult to crack, after being fully activated by pre-cracking in the lower layer and then entering the upper high-temperature forming zone for reaction, the purity of the product is still maintained at 45.91%.
[0048] Example 5 The difference from Example 1 is that in the first catalyst used in this example, the Mg:Al molar ratio of the magnesium-aluminum hierarchical porous support (commercially available) is 1:3, and the specific surface area is 186 m². 2 / g, total pore volume 0.42 cm³ 3 / g, a magnesium-aluminum hierarchical porous carrier was loaded with Fe-Ni bimetallic active components by equal volume impregnation method, with a total Fe-Ni metal loading of 6 wt% and a Fe to Ni mass ratio of 2:1. After impregnation and drying, it was calcined at 500 ℃ for 3 h. In the second catalyst, the specific surface area of the γ-alumina support (commercially available) is 220 m². 2 / g, total pore volume 0.5 cm³ 3 / g, the γ-alumina support was loaded with Co-Mo-Ni ternary metals using a stepwise impregnation process. First, the molybdenum precursor was impregnated and dried, then the co-cobalt and nickel precursors were co-impregnated, and finally calcined at 550 °C for 3 h. The total loading of Co, Mo and Ni metals was 4 wt%, and the mass ratio of Co:Mo:Ni was 3:1:2. The remaining processes and related parameters are the same as in Example 1.
[0049] The purity of carbon nanotubes in the product was found to be 46.1%, and the sample contained a small amount of fine, amorphous carbon impurities.
[0050] Example 6 The difference from Example 1 is that the first catalyst used in this example has a Mg:Al molar ratio of 3:1 and a specific surface area of 142 m² in the magnesium-aluminum hierarchical porous support (commercially available). 2 / g, total pore volume 0.36 cm³ 3 / g, a magnesium-aluminum hierarchical porous carrier was loaded with Fe-Ni bimetallic active components by equal volume impregnation method, with a total Fe-Ni metal loading of 18 wt% and a Fe to Ni mass ratio of 1:2. After impregnation and drying, it was calcined at 500 ℃ for 3 h. In the second catalyst, the specific surface area of the γ-alumina support (commercially available) is 220 m². 2 / g, total pore volume 0.5 cm³ 3 / g, the γ-alumina support was loaded with Co-Mo-Ni ternary metals using a stepwise impregnation process. First, a molybdenum precursor was impregnated, dried, and then co-impregnated with cobalt and nickel precursors, followed by calcination at 550 ℃ for 3 h. The total loading of Co, Mo, and Ni metals was 15 wt%, with a Co:Mo:Ni mass ratio of 5:2:1. The mass ratio of the first catalyst to the second catalyst was 2:1. The remaining processes and related parameters are the same as in Example 1.
[0051] The test results showed that the carbon nanotube product had a purity of 50.4%, with a small amount of carbon sphere impurities formed by local metal agglomeration.
[0052] Comparative Example 1 The difference from Example 1 is that in this comparative example, the second catalyst is only loaded in the upper forming reaction zone, and no catalyst is configured in the lower pre-cracking zone.
[0053] The remaining processes and related parameters are the same as in Example 1.
[0054] The test results showed that the carbon nanotube product had a purity of 33.7% and contained a large amount of amorphous carbon.
[0055] Comparative Example 2 The difference from Example 1 is that in this comparative example, the first catalyst is only loaded in the lower pre-cracking zone, and no catalyst is placed in the upper forming reaction zone.
[0056] The remaining processes and related parameters are the same as in Example 1.
[0057] The test results showed that the carbon nanotube product had a purity of 31.5%, and was mainly composed of flocculent amorphous carbon.
[0058] Comparative Example 3 The difference from Example 1 is that in this comparative example, the lower pre-cracking zone is filled with a second catalyst, and the upper forming reaction zone is filled with a first catalyst.
[0059] The remaining processes and related parameters are the same as in Example 1.
[0060] The test results showed that the carbon nanotube product had a purity of 35.2%, and the heavy hydrocarbons were not completely cracked.
[0061] See Figure 3 The thermogravimetric curves of the carbon nanotube products are shown. The horizontal axis represents temperature (°C), and the vertical axis represents the sample mass residual rate (%). The solid line (black) represents the carbon nanotube product obtained in Example 1, and the dashed line (gray) represents the carbon nanotube product obtained in Comparative Example 1. This is used to visually compare the differences in amorphous impurity content and high-temperature thermal stability between the two products. The results show that the carbon nanotube product obtained in Example 1 has a low high-temperature weight loss rate, fewer lattice structure defects, and excellent thermal stability.
[0062] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.
[0063] For the sake of simplicity, the method embodiments are described as a series of actions. However, those skilled in the art should understand that the present invention is not limited to the described order of actions, as some steps can be performed in other orders or simultaneously according to the present invention. Furthermore, those skilled in the art should also understand that the embodiments described in the specification are preferred embodiments, and the actions and components involved are not necessarily essential to the present invention.
[0064] The fluidized bed reactor and preparation method for the staged temperature-controlled coupled partitioned catalytic preparation of carbon nanotubes using mixed hydrocarbons provided by the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A fluidized bed reactor for the staged temperature-controlled coupled zoned catalytic preparation of hyperregular carbon nanotubes from industrial mixed hydrocarbons, characterized in that, The reactor is provided with a pre-pyrolysis zone and a forming reaction zone. The pre-pyrolysis zone is close to the reaction gas inlet, and the forming reaction zone is adjacent to the pre-pyrolysis zone. The pre-pyrolysis zone is equipped with a first catalyst, and the forming reaction zone is equipped with a second catalyst; The pre-pyrolysis zone and the molding reaction zone are equipped with independent temperature control components; The first catalyst is selected from a hierarchical porous magnesium-aluminum composite oxide supported Fe-Ni bimetallic catalyst; The second catalyst is selected from γ-alumina supported Co-Mo-Ni ternary metal catalysts.
2. The reactor for the staged temperature-controlled coupled zoned catalytic preparation of carbon nanotubes from industrial mixed hydrocarbons according to claim 1, characterized in that, In the first catalyst, the specific surface area of the hierarchical porous magnesium-aluminum composite oxide is 180 m². 2 / g~320 m 2 / g, total pore volume 0.35 cm³ 3 / g~0.65 cm 3 The molar ratio of Fe to Ni is 1:3 to 3:1; the total loading of Fe-Ni bimetallic compounds is 6 wt% to 18 wt%, and the mass ratio of Fe to Ni is 2:1 to 1:
2.
3. The reactor for the staged temperature-controlled coupled zoned catalytic preparation of carbon nanotubes from industrial mixed hydrocarbons according to claim 1, characterized in that, In the second catalyst, the specific surface area of the γ-alumina support is 260 m². 2 / g~400 m 2 / g, total pore volume is 0.4 cm³ 3 / g~0.7 cm 3 / g; the total loading of Co, Mo and Ni metals is 4 wt% to 15 wt%, and the mass ratio of Co, Mo and Ni is 3:1:2 to 5:2:
1.
4. The reactor for the staged temperature-controlled coupled zoned catalytic preparation of carbon nanotubes from industrial mixed hydrocarbons according to claim 1, characterized in that, In the first catalyst, the Mg to Al molar ratio of the hierarchical porous magnesium-aluminum composite oxide is 1:2, the total Fe-Ni bimetallic loading is 12 wt%, and the mass ratio of Fe to Ni is 1:
1. In the second catalyst, the total loading of Co, Mo, and Ni metals is 9 wt%, and the mass ratio of Co, Mo, and Ni is 4:2:
1.
5. The reactor for the staged temperature-controlled coupled zoned catalytic preparation of carbon nanotubes from industrial mixed hydrocarbons according to claim 1, characterized in that, The mass ratio of the first catalyst to the second catalyst is 1:2 to 2:
1.
6. A method for preparing carbon nanotubes by segmented temperature-controlled coupled zoned catalysis of industrial mixed hydrocarbons, characterized in that, The preparation method includes: The temperature of the pre-pyrolysis zone of the reactor described in any one of claims 1-5 is controlled at 650 ℃ to 700 ℃, and the temperature of the forming reaction zone is controlled at 750 ℃ to 800 ℃. Liquid hydrocarbon feedstock in industrial mixed hydrocarbon feedstock is completely vaporized into gaseous material, and then mixed with gaseous low-carbon hydrocarbon feedstock. The resulting homogeneous mixed reaction gas is fed into the reactor through the reaction gas inlet along with the carrier gas. The homogeneous mixed reaction gas is then catalyzed by the first catalyst packed in the pre-cracking zone and the second catalyst packed in the forming reaction zone to obtain carbon nanotubes.
7. The method for preparing carbon nanotubes by segmented temperature-controlled coupled zoned catalysis of industrial mixed hydrocarbons according to claim 6, characterized in that, The carrier gas is selected from nitrogen.
8. The method for preparing carbon nanotubes by segmented temperature-controlled coupled zoned catalysis of industrial mixed hydrocarbons according to claim 6 or 7, characterized in that, The flow rate of the carrier gas is 500 mL / min to 800 mL / min.
9. The method for preparing carbon nanotubes by segmented temperature-controlled coupled zoned catalysis of industrial mixed hydrocarbons according to claim 6, characterized in that, The purity of carbon nanotubes in the solid product obtained by conversion is not less than 45%.
10. The method for preparing carbon nanotubes by segmented temperature-controlled coupled zoned catalysis of industrial mixed hydrocarbons according to claim 5, characterized in that, The industrial mixed hydrocarbon feedstock is derived from resource recovery materials such as coal chemical tail gas, polymer pyrolysis waste liquid, or petrochemical waste oil.